The Effect of Central and Peripheral Fatigue on Coordination of Student Athletes - Ali Zahiri; Mehdi Shahbazi; Mohammad Reza Kordi; Jamal Fazel Kalkhoran (University of Tehran, 2017)
The aim of this study was to investigate the effect of central and peripheral fatigue on motor coordination in collegiate athletes. The population consisted of all the students of Faculty of Physical Education and Sports Sciences of University of Tehran and 24 subjects were selected by convenience sampling method. They were randomly divided into two groups (central and peripheral fatigue) depending on the type of fatigue after a bimanual motor coordination pretest. Bimanual motor coordination posttest was performed after the intervention for 12 hours. In order to investigate the differences between the groups, independent t test and to determine differences within a group, dependent t test were used with the significance level of P≤0.05. Results showed that the mean time to complete the task and the timing error in central (P=0.004) and peripheral (P=0.0001) fatigue groups significantly increased compared with the pretest. Also, a significant difference in bimanual motor coordination between the two groups was observed in posttest (P=0.006). According to the results, it is suggested that athletes' training and working programs should be planned so that they include exercises to increase mental stamina along with physical exercises and that the athletes can provide their optimal performance in different conditions.